In vitro application of Eruca vesicaria subsp. sativa leaf extracts and associated metabolites reduces the growth of Oomycota species involved in Kiwifruit Vine Decline Syndrome - Mian, Giovanni; Zuiderduin, Kathryn; Barnes, Luke S.; Loketsatian, Supasan; Bell, Luke; Ermacora, Paolo; Cipriani, Guido (Frontiers in Plant Science, 2023)
This study aimed to determine whether leaf extracts from seven Eruca vesicaria subsp. sativa cultivars and their biochemical active compounds (glucosinolates and downstream-derived products) inhibit mycelia growth of three well-known pathogenic oomycetes, Phytopythium chamaehyphon, Phytopythium vexans and Phytophthora citrophthora; being the most significant in the development of Kiwifruit Vine Decline Syndrome (KVDS). Leaf extract quantity of 10, 20 and 30 mg were inoculated in Petri dish (90 mm Ø, each 22 mL of liquid medium -Potato Dextrose Agar), for in vitro bioassays. A pathogen plug was placed in the centre of each plate and the Oomycota colony perimeter was marked 5 days after inoculation. Radial colony growth was measured from 4 marks per plate 5, 10, and 15 days after inoculation, further elaborated with Image J software image analysis.Growth rates for all strains were inhibited by around 67% after 15 days. This was most pronounced when applying the highest concentration of leaf extract. By using Liquid Chromatography Mass Spectrometry (LC-MS) and Gas Chromatography Mass Spectrometry (GC-MS), fifteen glucosinolate compounds, of which glucosativin was found in the highest quantity, were identified. Concentrations of hydrolysis products produced by leaves (erucin and sativin) were also investigated, and were significantly associated with colony radial growth, especially towards Pp. chamaehyphon and Pp. vexans. Three downstream products of glucosinolates (two pure isothiocyanates, AITC and PEITC; and one indole I3C; all commonly present in Brassicaceae) were also tested, and a statistically significant inhibition of growth was observed at the highest concentration (0.6 µL).